Interest rate determination in the interbank market - Vítor Gaspar; Gabriel Pérez Quirós; Hugo Rodríguez Mendizábal (European Central Bank (ECB), 2004)
The purpose of this paper is to study the determinants of equilibrium in the market for daily funds. We use the EONIA panel database which includes daily information on the lending rates applied by contributing commercial banks. The data clearly shows an increase in both the time series volatility and the cross section dispersion of rates towards the end of the reserve maintenance period. These increases are highly correlated. With respect to quantities, we find that the volume of trade as well as the use of the standing facilities are also larger at the end of the maintenance period. Our theoretical model shows how the operational framework of monetary policy causes a reduction in the elasticity of the supply of funds by banks throughout the reserve maintenance period. This reduction in the elasticity together with market segmentation and heterogeneity are able to generate distributions for the interest rates and quantities traded with the same properties as in the data.
Keywords: E52; E58; 330; Eonia panel; monetary policy instruments; Overnight interest rate